Yesus Sungguh Allah, Sungguh Manusia. Tinjauan Teologis Menurut Perspektif Islam dan Katolik - Darman, Andrianus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2021)
Both the Islamic and Catholic Scriptures speak about Jesus. They recognize Jesus as the revelation of God’s Self to humans. However, Islam only recognizes Him as an ordinary human being, while Catholicism recognizes Him as truly God and truly human. Why do these two major religions (Islam and Catholicism) have different views about Jesus? The Qur’an says that Jesus was not the third Person of the Trinity, not the Son of God, and was not even a god. Islam believes that Jesus was just an ordinary man. Al-Ghazali added that God is perfect in Himself. The nature of humanity cannot be united like divinity. Catholicism recognizes Jesus as truly God and truly human. The explanation of the doctrine can be found in the description of the historical Jesus and faith. In Christian faith, Jesus was historically believed to be both God’s revelation of himself and human’s response to this revelation, through the event of the Incarnation. The mystery of Incarnation shows that God loves human beings. The article argues then that only through this mystery of Incarnation in Jesus, one could approach God who is beyond human understanding.